2014
DOI: 10.1177/2051415814560188
|View full text |Cite
|
Sign up to set email alerts
|

Day-case holmium laser enucleation of the prostate

Abstract: In 2011 day-case prostate surgery was selected for financial incentives in the UK by the Department of Health Payment by Results (PbR) scheme, with a target of 30% of holmium laser enucleation of the prostate (HoLEP) procedures as day cases for 2011-2012, increasing to 90% within three years. The objective was to determine the feasibility and safety of day-case HoLEP. Patients and methods: All patients presenting to an experienced HoLEP surgeon and requiring prostatic surgery were considered for day-case HoLEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
0
15
1
Order By: Relevance
“…In a larger study with 184 patients by Cynk et al, 14 the authors demonstrated an overall successful day-case rate of 49.5%, greater than that of our study. Patients were excluded on the basis of medical comorbidity including ASA grade greater than 3 and anticoagulation that could not be stopped, but additionally logistical factors (i.e.…”
Section: Discussioncontrasting
confidence: 66%
“…In a larger study with 184 patients by Cynk et al, 14 the authors demonstrated an overall successful day-case rate of 49.5%, greater than that of our study. Patients were excluded on the basis of medical comorbidity including ASA grade greater than 3 and anticoagulation that could not be stopped, but additionally logistical factors (i.e.…”
Section: Discussioncontrasting
confidence: 66%
“…Only two studies 20,36 did not report failure events among the patients included in their analysis and therefore were not considered in the quantitative synthesis. In total, 18 studies 18,19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]37 reporting data on immediate hospital readmission and/or inability to discharge after the endoscopic procedure presented different FR estimates ranging from 1.7% to 51.1%. Demographic and perioperative characteristics of the 18 studies analyzed are further presented in Table 2.…”
Section: Cumulative Fr Of Outpatient Bph Surgical Managementmentioning
confidence: 99%
“…Subgroup analysis according to type of surgical technique. In total, five studies [32][33][34][35]37 implementing Greenlight, nine articles with HoLEP, [23][24][25][26][27][28][29][30][31] and four with TURP 18,19,21,22 were, respectively, reviewed. Test for differences among subgroups revealed the presence of a SAFETY OF BPH SURGERY ON OUTPATIENT SETTING statistical difference among the three different approaches (Q = 13.32, df = 2, p < 0.001).…”
Section: Cumulative Fr Of Outpatient Bph Surgical Managementmentioning
confidence: 99%
See 2 more Smart Citations